Acute serous tamponade after paraesophageal hernia repair reoperation. (9th August 2018) - Makey, Ian A; Beers, Kevin; Eilers, Amanda; Thomas, Mathew
Abstract : Cardiac tamponade is a common complication after cardiac surgery and is usually caused by bleeding or thrombus in the early postoperative period. Postoperative serous tamponade is more rare and usually of gradual onset. We report an unusual and life-threatening case of serous tamponade occurring on postoperative day 1 following a third-time paraesophageal hernia repair.